Galaxy and Mass Assembly (GAMA): active galactic nuclei in pairs of galaxies - Gordon, Yjan A.; Owers, Matt S.; Pimbblet, Kevin A.; Croom, Scott M.; Alpaslan, Mehmet; Baldry, Ivan K.; Brough, Sarah; Brown, Michael J.I.; Cluver, Michelle E.; Conselice, Christopher J.; Davies, Luke J. M.; Holwerda, Benne W.; et al. (Oxford University Press, 2017)
There exist conflicting observations on whether or not the environment of broad and narrow line AGN differ and this consequently questions the validity of the AGN unification model. The high spectroscopic completeness of the GAMA survey makes it ideal for a comprehensive analysis of the close environment of galaxies. To exploit this, and conduct a comparative analysis of the environment of broad and narrow line AGN within GAMA, we use a double-Gaussian emission line fitting method to model the more complex line profiles associated with broad line AGN.We select 209 type 1 (i.e., unobscured), 464 type 1.5-1.9 (partially obscured), and 281 type 2 (obscured) AGN within the GAMA II database. Comparing the fractions of these with neighbouring galaxies out to a pair separation of 350 kpc h-1 and delta z < 0:012 shows no difference between AGN of different type, except at separations less than 20 kpc h-1 where our observations suggest an excess of type 2 AGN in close pairs. We analyse the properties of the galaxies neighbouring our AGN and find no significant differences in colour or the star formation activity of these galaxies. Further to this we find that sigma 5 is also consistent between broad and narrow line AGN. We conclude that the observations presented here are consistent with AGN unification.